BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN BERKUNJUNG PADA OBJEK WISATA PANTAI TANJUNG KARANG - DJESIKA, DJESIKA (Fakultas Ekonomi Universitas Tadulako, 2019)
This study aims to determine the effect of the service marketing mix on consumer decisions to visit the Tanjung Karang coastal tourism object in Donggala Regency. The independent variables used in this study are product / service, price, place, promotion, person, process, and physical evidence. While the dependent variable is the decision to visit (Y). This type of research is quantitative. The research method is descriptive causal. The sample used in this study were 80 respondents with the sampling form using accidental sampling technique. Multiple linear regression analysis method. The results of this study indicate that the service marketing mix simultaneously consisting of products, prices, places, promotions, people, processes, and physical evidence has a significant effect on the decision to visit the Tanjung Karang coastal tourism object in Donggala Regency. And partially there is no relationship between product variables, prices, places, promotions, people, processes, and physical evidence.